(untitled) (American Journal of Islam and Society, 2008)
This important book critically examines the religious and political thought of Mahmud Muhammad Taha, a significant twentieth-century reformist thinker who is hardly known outside of Sudanese studies. Other works in English on Taha include Abdullahi al-Na`im’s translated The Second Message of Islam (Syracuse University Press: 1987), written by a disciple whose own reformist positions derive from Taha’s methodology and thought. This study provides an introduction to Taha’s thought for scholars of twentieth-centuryMuslim reformers. It highlights the radical nature of his Sufi-grounded thought and the originality of his interpretations of the Qur’an and the hadith based upon Muslim scholars as well as western Darwinian and Marxist-Hegelian thought. The author stresses the importance and originality of Taha’s thoughtwithin the broader context of the contemporary Muslim world. His appearance on the scholarly “radar screen” has not yet fully been realized; indeed, al`Na`im has drawn more attention in theWest than his mentor Taha ever did. As the founder of the nationalist al-Hizb al-Jamhuri in 1945, which later became the Republican Brotherhood (al-Jamhouriyeen), Taha was both a significant political figure and a controversial theologian who was famously tried and executed for the “crime” of apostasy in 1985. His execution is widely viewed as having sparked the democratic uprising (intifada) that overthrew Numeiri’s military dictatorship, which had engineered his execution ...